Engineering spatially-confined conduits to tune nerve self-organization and allodynic responses via YAP-mediated mechanotransduction - Xiaobin Luo; Jia Yang; Yonggang Zhao; Toshitatsu Nagayasu; Junlin Chen; Peilun Hu; Zhi He; Zifan Li; Jun Wu; Zhe Zhao; Guman Duan; Xiaodan Sun; et al. (Nature Communications)
Abstract Chronic allodynia stemming from peripheral stump neuromas can persist for extended periods, significantly compromising patients’ quality of life. Conventional managements for nerve stumps have demonstrated limited effectiveness in ensuring their orderly termination. In this study, we present a spatially confined conduit strategy, designed to enhance the self-organization of regenerating nerves after truncation. This innovative approach elegantly enables the autonomous slowing of axonal outgrowth in response to the gradually constricting space, concurrently suppressing neuroinflammation through YAP-mediated mechanotransduction activation. Meanwhile, the decelerating axons exhibit excellent alignment and remyelination, thereby helping to prevent failure modes in nerve self-organization, such as axonal twisting in congested regions and overgrowth beyond the conduit’s capacity. Additionally, proteins associated with mechanical allodynia, including TRPA1 and CGRP, exhibit a gradual reduction in expression as spatial constraints tighten, a trend inversely validated by the administration of the YAP-targeted inhibitor Verteporfin. This spatially confined conduit strategy significantly alleviates allodynia, thus preventing autotomy behavior and reducing pain-induced gait alterations.